(m+2)(m+3)=(m+2)(m-2) what is the answer please

\( (m+2)(m+3)=(m+2)(m-2)\\\\m^2+3m+2m+6=m^2-4\\\\m^2-m^2+5m=-4-6\\\\5m=-10\ \ \ \ /:5\\\\m=-2 \)

The first time you look at this, you would think that you can just cancel the
(m+2) off of each side. But then you’re left with  (m+3) = (m-2), and there’s
no solution for this.   So you have to go back and do it the hard way.

Expand each side of the equation. (Clear the parentheses. )

m² + 5m + 6 = m² - 4

Subtract m² from each side:

5m + 6 = -4

Subtract 6 from each side:

5m = -10

Divide each side by 5:

m = -2



RELATED: